PENGARUH PAJAK, TUNNELING INCENTIVE DAN MEKANISME BONUS PADA KEPUTUSAN TRANSFER PRICING PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2018)
The aim of this research is to test the influence of tax tunneling incentive and bonus scheme on transfer pricing decision in manufacture companies that listed at Indonesian Stock Exchange. Sample selection was using purposive sampling with final sample 44 from 2012 observation. The result shows that tax and tunneling incentive have an influence on transfer pricing decision, besides than bonus scheme doesn’t have an influence on transfer pricing decision. The determination coefficient is 31,8% that is reflect to variation of tax, tunneling and bonus scheme affect transfer pricing decision. The influence of tax and tunneling is also statistically significant affect transfer pricing. Otherwise the influence of tax and bonus scheme doesn’t have statistically significant affect transfer pricing. The findings give any opportunities to next researchers to investigate the effect of any others variable on transfer pricing decision, such as bonus scheme that based on income. The measurement of transfer pricing using sales to related parties is also relevant proxy and also investigate the effect of any others variable on transfer pricing decision, such as tariffs to the next research.